Expanding on Phenomenological Research Findings on Adult Learners’ Experiences with the Portfolio Process - Benjamin A Jimenez (Adult Education Research Conference, 2018)
This paper is a discussion on the finding that the participants created new and different learning on previously attained knowledge, skills, or abilities via the portfolio process.
Keywords: Reflection-based learning; portfolio; active reflection; new meaning-making